Reforma da previdência brasileira de 2019: possíveis implicações e riscos da perda de direitos - Meyer, Fernanda Aline Schwartzbach (2022)
The current investigation is the result of a study about the social security and its approach to social rights and social justice, providing a perspective along the issue of social security and its reform in 2019. Thus, the principles that guide this order will be introduced, as well as the reform project that was presented and judged in 2019. The initial proposal (Proposed Constitutional Amendment 06/2019), legislation prior to the reform and the current regulation (Constitutional Amendment 103/2019) have been detailed. Regarding the methodology, a bibliographic has been carried out based on studies already performed, considering books, articles, and documents relevant to the focus of the paper. So, a social security policy was analyzed, seeking to investigate and unveil points of the referred 2019 reform, based on the hypothesis that it presents elements that deprived Brazilian population's rights, although already consolidated in constitutional legislation, affecting considerably the lives of countless Brazilian citizens.